Evaluating COVID-19–Environment Fit - Saghazadeh, Amene; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
Spring came and went; the COVID-19 pandemic is still an inhabitant of the world, and its tendency to infect individuals is preserved in numbers; so does the case fatality rate continues to increase. While a long list of facts provided by the clinical and medical sciences have remained unable to resolve the problem, recognizing environmental issues concerning COVID-19 resistance and adaptation might be a flash of lighting the nature of COVID-19 and its ideas of fitness. Here, we summarize the current state of the science of environment related to the causative pathogen of COVID-19, SARS-CoV2, as follows. SARS-CoV2 i. survives in water, ii. mainly spreads via the droplet route, and to a lesser extent, from touching contaminated surfaces, iii. transmission via droplets occurs within the interpersonal distance of two meters and beyond, iv. can more easily spread and cause more severe phenotypes of disease under higher-polluted, low-temperature, and low-humidity conditions, v. can spread under high-temperature conditions, and vi. transmission might be moderated by pollen-derived immune responses and lockdown-mediated air quality improvement.